2017
DOI: 10.1007/s12253-017-0332-1
|View full text |Cite
|
Sign up to set email alerts
|

The Presence of ALK Alterations and Clinical Relevance of Crizotinib Treatment in Pediatric Solid Tumors

Abstract: Soft tissue sarcomas (STS) and neuroblastomas (NBL), are childhood malignancies still associated with poor prognoses despite the overall improvement in childhood tumor survival of the past decades. Anaplastic lymphoma kinase (ALK) inhibition is promising new strategy to improve the outcome of these pediatric tumors. Eighteen histologic samples of pediatric STS and 19 NBL patients were analyzed for ALK abnormalities using fluorescent in situ hybridization (FISH) with break-apart probes and immunohistochemistry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 25 publications
0
16
0
1
Order By: Relevance
“… 7 The reported case is particularly interesting and innovative because molecular pathology confirmed ALK-EML4 translocation opening up the possibility for targeted therapy with a proteinase inhibitor. 8 As a consequence, the applied systemic therapy was from the outset combining conventional chemotherapy with targeted drugs as crizotinib.…”
Section: Discussionmentioning
confidence: 99%
“… 7 The reported case is particularly interesting and innovative because molecular pathology confirmed ALK-EML4 translocation opening up the possibility for targeted therapy with a proteinase inhibitor. 8 As a consequence, the applied systemic therapy was from the outset combining conventional chemotherapy with targeted drugs as crizotinib.…”
Section: Discussionmentioning
confidence: 99%
“…If conservative treatment is ineffective, simple tumor resection or partial nephrectomy would be feasible. It was recently reported that Myofibroblastic tumour patients had promising results with crizotinib treatment, so tyrosine kinase inhibitors (TKIs) can be used as an alternative to conservative treatment[13,14]. For tumors that are difficult to completely resect, TKIs can be also used as neoadjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Crizotinib is approved for the treatment of ALK -rearranged non-small cell lung cancer, but the majority of ALK gene aberration in RMS is copy number gain [ 16 ]. There are limited clinical trial data on the effect of crizotinib on ALK-positive RMS and its efficacy on RMS requires further investigation [ 17 ].…”
Section: Discussionmentioning
confidence: 99%